Dual Targeting of Cell Growth and Phagocytosis by Erianin for Human Colorectal Cancer - Sun Y; Li G; Zhou Q; Shao D; Lv J; Zhou J (Dove Medical Press, 2020)
Yihan Sun,1 Guofeng Li,1 Qi Zhou,1 Danyue Shao,2 Jingwei Lv,3 Jianhua Zhou1 1School of Traditional Chinese Medicine, Changchun University of Chinese Medicine, Changchun 130117, People’s Republic of China; 2Second School of Clinical Medicine, Beijing University of Chinese Medicine, Beijing 100029, People’s Republic of China; 3Jilin Ginseng Academy, Changchun University of Chinese Medicine, Changchun 130117, People’s Republic of ChinaCorrespondence: Jianhua ZhouSchool of Traditional Chinese Medicine, Changchun University of Chinese Medicine, 1035 Boshuo Road, Jingyue National High-Tech Industrial Development Zone, Changchun 130117, People’s Republic of ChinaTel +86-15948000805Email jianhuazhou1334@sohu.comObjective: To investigate the effect of erianin on tumor growth and immune response in human colorectal cancer cells (CRC).Methods: The effect of erianin on tumor growth was determined by CCK8 and colony formation assay. Western blotting was used to evaluate the expression levels of relevant proteins and qRT-PCR was used to evaluate the mRNA level of the relevant gene. The transcriptional activity of β-catenin was determined by dual-luciferase reporter assay. Cellular thermal shift assay was used to quantify drug–target interactions. The cell surface CD47 was assessed by flow cytometry. The enrichment of H3K27 acetyl marks on CD47 promoter was evaluated by chromatin immunoprecipitation assay. Phagocytosis assay was used to determine the phagocytic activity of macrophage. In vivo role of erianin was studied on xenograft models.Results: We found that erianin significantly decreased cell survival, colony formation, induced cell cycle arrest, and led to cell apoptosis in SW480 and HCT116 cells. Mechanism analysis demonstrated that erianin inhibited the nuclear translocation and transcriptional activity of β-catenin, which might result from erianin-β-catenin interaction. In addition, the downstream gene expressions, such as c-Myc and cyclin D1, was decreased. More interestingly, erianin decreased the expression of CD47 by regulating H3K27 acetyl marks enrichment on CD47 promoter. Consequently, macrophage-mediated phagocytosis was increased. Our in vivo experiments further confirmed the inhibitory effect of erianin on tumor growth.Conclusion: In summary, erianin could inhibit CRC cells growth and promoted phagocytosis, which suggested erianin as a potential therapeutic strategy for CRC patients.Keywords: erianin, colorectal cancer, β-catenin, CD47, macrophage